Onboard visual-based navigation system for power line following with UAV. (13th March 2018) - Cerón, Alexander; Mondragón, Iván; Prieto, Flavio
The details of an onboard visual-based navigation system that allows an unmanned aerial vehicle to perform power line following are presented in this article. A histogram of oriented segments method was developed to establish the main angle orientation of power lines. The histogram of oriented segment is also used to discard segments that are not power lines in the images. The components of the unmanned aerial vehicle flight system which include the platform configuration and the hardware used are also presented. A set of tests were designed to validate the methods and the overall system. The system was tested with a sequence of images taken from different perspectives in real inspection tasks. Tests were performed with images taken using an unmanned aerial vehicle with a camera, pointing vertically downward, and also using different kinds of cameras. The techniques developed for unmanned aerial vehicle navigation were employed over power lines using a multirotor. The results showed that a vision system based on the developed techniques is able to give important information to an unmanned aerial vehicle in order to perform autonomous flight missions.